General environmental aspects of the textile industry - Kriuchkova, Valeriia (National Technical University "Kharkiv Polytechnic Institute", 2024)
The textile industry is one of the most important sectors of the national economy, both in Ukraine and in the whole world. The development of this industry in Ukraine is of great importance for the post-war economic recovery. Technological processes for the production of finished goods are mostly massive in nature and are characterised by speed and mobility. However, despite its clear economic advantages, the textile industry faces a number of serious environmental issues. These include resource intensity, wastewater, soil and air pollution, as well as excessive production and consumption waste. These and other problems of the industry contradict the principles of sustainable development and need to be addressed.
Keywords: textile industry; sustainable development; circular economy; waste recycling; waste; ecology